Donation Fundraising Strategies Kitabisa.Com Through Crowdfunding - Fadilla, Atria Nuraini; Indriati, Lisa (VCD, 2019)
Kitabisa.com is an online crowdfunding platform in Indonesia. The success of its campaign cannot be separated from the role of fundraising strategies which are carried out through story-based publications. On that basis, this research was conducted by examining the storytelling techniques with visual approach on Kitabisa.com campaign. This research is a descriptive qualitative research with data collection method through observation and literature studies. After collecting data through purposive sample criteria, three types of campaigns were obtained, all of which fall into the category of Medical and Health Assistance. The three types of examined campaigns, then categorized and interpreted in matrix analysis. Through analytical studies, it was found that the audience's emotions effectively were built through persuasive narratives with psychodynamic strategies. The results of this study can be used as a reference in creating a similar fundraising campaign.